Honestum is as Honestum Does: Reid, Hume – and Mandeville?!. Issue 1 (March 2014) - Edwards, Jeffrey
<x xml:space="preserve">Abstract</x> How are we to understand Thomas Reid in relation to Bernard de Mandeville? I answer this question by considering two components of the assessment of Hume's theory of morals that Reid provides in his Essays on the Active Powers of Man: first, Reid's claim that Hume's system of morals cannot accommodate the Stoic conception of moral worth (honestum); second, Reid's charge that Hume's account of morally meritorious action leads to an inflated and incoherent version of Epicurean virtue theory. I thus determine the character of Reid's relation to Mandeville by examining the Stoic and anti-Epicurean assumptions involved in Reid's criticism of Hume's ethics.